PERAN MUSYRIF DALAM MEMBENTUK KARAKTER DISIPLIN SANTRI PONDOK PESANTREN IBNUL QAYYIM PUTRA TEGALYOSO PIYUNGAN BANTUL YOGYAKARTA - Rubini; M. Rifa’i (Salam Institute Islamic Studies, 2024)
This  study  aims  to  determine  the  role  of  musyrif  in  shaping  the  disciplinary character of students at Ibnul Qoyyim Putra Tegalyoso Piyungan  Islamic Boarding School Yogyakarta as well as the supporting and inhibiting factors.Data  were  obtained  using  documentation,  interviews,  and  observation  methods, while the subjects of this study were five musyrifs of Ibnul Qoyyim Putra Islamic Boarding  School  in  Yogyakarta.  Data  analysis  using  the  Miles  and  Huberman model begins with data reduction, data presentation, and data analysis in the form of descriptions. Ended with drawing conclusions/verification between theory and practice that occurs in the field.The results showed that the role of musyrif in shaping the disciplinary character of the students of Ibnul Qoyyim Putra Tegalyoso Piyungan Bantul Yogyakarta Islamic Boarding  School  is  as  a  director,  facilitator,  informator,  motivator,  initiator. Supporting factors in the formation of the disciplinary character of students of Ibnul Qoyyim  Putra  Islamic  Boarding  School  are  the  tole  model  of  a  musyrif,  the implementation  of  active  activities,  as  well  as  communication  and  assistance  to students. inhibiting  factors in the formation of the disciplinary character of students of Ibnul Qoyyim Putra Islamic Boarding School are the lack of communication with santri guardians, the lack of awareness of students regarding their purpose in the boarding school, and facilities and infrastructure in the form of fences that have not surrounded the Ibnul Qoyyim Putra Islamic Boarding School.